Bridging the gap: monthly telephone calls to enhance collaboration between primary care physicians and psychiatrists - Kamini Vasudev; Stephanie Fernando (BMJ Open Quality, 2025)
Background The integration of mental health services within primary care settings is a growing priority in Canada, driven by the need to improve access and ensure comprehensive patient-centred care. This year-long pilot quality improvement (QI) project was conducted to examine the feasibility and impact of introducing monthly telephone consultations between primary care physicians (PCPs) and psychiatrists working at a secondary care regional hospital in Ontario, Canada.Methods PCPs were connected with a team of psychiatrists via email on a voluntary basis. Once connected, PCPs were encouraged to contact psychiatrists by text or email to book monthly telephone consultation for patient care.Results A total of seven PCPs and five psychiatrists participated in this project. A total of 66 patients were discussed via telephone consultations between PCPs and psychiatrists and 11 of these patients were referred to psychiatry for further assessment. The number of referrals to psychiatry O-P service from the seven PCPs involved in this pilot decreased from 83 for the period of November 2021 to October 2022 to 53 for the period of this project, that is, November 2022 to October 2023.There were initial challenges in scheduling consultations due to busy practices. After the first few months of regular monthly contact, three psychiatrists reported fewer ongoing contacts with PCPs and that PCPs email them on an as needed basis. Two psychiatrists continued to have ongoing 4–6 weeks contact with their assigned PCP, discussing on average 3–4 patients, after 1 year.Psychiatrists found the telephone meetings productive and the PCPs were appreciative of the support provided and were willing to take over the primary care of some patients under the care of the psychiatrists, who had medical needs but no PCP.Conclusion This pilot QI project confirms the feasibility and successful collaborations between PCPs and psychiatrists through monthly phone calls.